Evaluation of cardiac biomarkers in smokers and non-smokers with chronic periodontitis - Ameen, Mazen; Attia, Alaa Moustafa; Felimban, Anas; Al-Dweghri, Tariq; Fattni, Abdulrahman; Azab, Ehab; Baz, Sameh; Dardir, Ahmed (International Journal of Health Sciences, 2020)
Objectives: The present study aimed to assess the levels of the cardiac biomarkers in smokers versus non-smokers chronic periodontitis (CP) patients and periodontally healthy subjects, also to correlate cardiac biomarkers level with the severity of CP. Methods: Eighty selected individuals were divided into three groups: Smokers CP (28), non-smokers CP (32), and healthy control subjects (20). The CP evaluated clinically by plaque index (PI), bleeding index (BI), clinical attachment loss (CAL), and pocket depth (PD). Serum levels of cardiac biomarkers were assayed for the following: Aspartate transaminase (AST), alanine transaminase (ALT), troponin-I (Tr-I), creatinine kinase (CK), and lactate dehydrogenase (LDH). Results: The statistical analysis of the investigated biomarkers showed that ALT and AST significantly increased in smokers versus non-smokers CP patients (P ≤ 0.05). In addition, the other biomarkers (Tr-I, CK, and LDH) showed a non-significant increase in smokers compared with non-smokers periodontitis patients (P ≥ 0.05). Furthermore, the mean values of all biomarkers, Tr-I, ALT, AST, LDH, and CK, expressed highly significant comparisons (P ≤ 0.01) in smokers and non-smokers CP patients against healthy subjects. Conclusion: The present study suggested that the cardiac biomarkers affected by CP and worse aggravated by the presence of smoking that could play a bidirectional effect on periodontitis and cardiovascular (CV) conditions. Further researches are needed to elucidate the efficacy of periodontal treatment and serum cardiac biomarkers in systemically healthy and diseased CV patients.